PENGARUH METODE PEMBELAJARAN DAN STATUS GIZI TERHADAP HASIL BELAJAR MELEMPAR BOLA - ARIESNA, RACHMAT DODY; KUSUMAWATI, OKTARIA (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2018)
This study aimed to know the difference between playing and learning methods of exploratory learning methods to learning outcomes throwing the ball. In addition, this study also aimed to determine the effect of nutritional status of these two learning methods mentioned above. This research was conducted at SDN 8 Gedung Air, Bandar Lampung City in 2018.  The method used is an experiment with a 2x2 factorial analysis through random sampling with a sample of 24 students. The analysis technique used is the analysis of variance (ANAVA) two-way, followed by Turkey test at the 0.05 level of significance. This study concludes that overall there are significant effect between the methods of learning to play with the exploration of learning methods to learning outcomes throwing the ball.  This study also concluded that the interaction between teaching methods and nutritional status.